(untitled) - Birkhoff, Garrett (New York, 1970)
This book attempts to present those ideas and techniques of modern algebra which have proved most useful for these areas. Although some separation is inevitable between the discussion of mathematical principles and their applications.
Keywords: Algebra,Đại số